Sero-prevalence of 19 infectious pathogens and associated factors among middle-aged and elderly Chinese adults: a cross-sectional study - Yao, P; Millwood, I; Kartsonaki, C; Mentzer, A; Allen, N; Chen, Y; Walters, R; Yang, L; Chen, Z (BMJ Publishing Group, 2022)
Objectives To systematically assess the sero-prevalence and associated factors of major infectious pathogens in China, where there are high incidence rates of certain infection-related cancers. Design Cross-sectional study. Setting 10 (5 urban, 5 rural) geographically diverse areas in China. Participants A subcohort of 2000 participants from the China Kadoorie Biobank. Primary measures Sero-prevalence of 19 pathogens using a custom-designed multiplex serology panel and associated factors. Results Of the 19 pathogens investigated, the mean number of sero-positive pathogens was 9.4 (SD 1.7), with 24.4% of participants being sero-positive for >10 pathogens. For individual pathogens, the sero-prevalence varied, being for example, 0.05% for HIV, 6.4% for human papillomavirus (HPV)-16, 53.5% for Helicobacter pylori (H. pylori) and 99.8% for Epstein-Barr virus . The sero-prevalence of human herpesviruses (HHV)-6, HHV-7 and HPV-16 was higher in women than men. Several pathogens showed a decreasing trend in sero-prevalence by birth cohort, including hepatitis B virus (HBV) (51.6% vs 38.7% in those born <1940 vs >1970), HPV-16 (11.4% vs 5.4%), HHV-2 (15.1% vs 8.1%), Chlamydia trachomatis (65.6% vs 28.8%) and Toxoplasma gondii (22.0% vs 9.0%). Across the 10 study areas, sero-prevalence varied twofold to fourfold for HBV (22.5% to 60.7%), HPV-16 (3.4% to 10.9%), H. pylori (16.2% to 71.1%) and C. trachomatis (32.5% to 66.5%). Participants with chronic liver diseases had >7-fold higher sero-positivity for HBV (OR=7.51; 95% CI 2.55 to 22.13). Conclusions Among Chinese adults, previous and current infections with certain pathogens were common and varied by area, sex and birth cohort. These infections may contribute to the burden of certain cancers and other non-communicable chronic diseases.